Electrode for secondary battery, secondary battery including same, and method for manufacturing electrode

By employing a dry mixing process with a first and second binder of distinct glass transition temperatures, the electrodes achieve improved tensile strength and reduced resistance, addressing the limitations of conventional wet-manufactured electrodes.

JP7604064B2Active Publication Date: 2024-12-23LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022575453
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-15
Filing Date
2021-10-19
Publication Date
2024-12-23
Estimated Expiration
2041-10-19

AI Technical Summary

Technical Problem

Conventional secondary battery electrodes face issues with tensile strength and resistance due to the use of wet manufacturing methods that require high-temperature heat treatments, which can damage metal oxides, necessitating the development of dry-manufactured electrodes with improved properties.

Method used

The electrodes are composed of a dry mixed layer of active materials, conductive materials, and binders, utilizing a first binder and a second binder with different glass transition temperatures, applied in specific ratios and temperatures to enhance tensile strength and reduce resistance.

Benefits of technology

The solution results in electrodes with enhanced tensile strength and reduced resistance, improving flexibility and productivity while preventing damage to active materials during manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604064000003
    Figure 0007604064000003
  • Figure 0007604064000004
    Figure 0007604064000004
  • Figure 0007604064000005
    Figure 0007604064000005
Patent Text Reader

Abstract

An electrode for a secondary battery according to one embodiment of the present invention includes an electrode current collector; and an electrode layer located on the electrode current collector. The electrode layer includes an electrode composition in which an active material, a conductive material, and a binder are dry-mixed. The binder includes a first binder and a second binder, the first binder and the second binder being different from each other, and the second binder being attached to a surface of the first binder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Cross-reference to related applications] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0139305 filed on October 26, 2020, and Korean Patent Application No. 10-2021-0137513 filed on October 15, 2021, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to an electrode for a secondary battery, a secondary battery including the same, and a method for manufacturing the electrode, and more specifically to an electrode for a secondary battery having improved tensile strength and resistance reduction effect, a secondary battery including the same, and a method for manufacturing the electrode. [Background technology]

[0003] Due to technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] In particular, secondary batteries have attracted much attention as energy sources not only for mobile devices such as mobile phones, digital cameras, notebook computers, and wearable devices, but also for power plants such as electric bicycles, electric cars, and hybrid electric cars.

[0005] In addition, as interest in environmental issues grows, much research is being conducted on electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution. Nickel-metal hydride secondary batteries are mainly used as the power source for such electric vehicles and hybrid electric vehicles, but active research is being conducted on the use of lithium secondary batteries with high energy density and discharge voltage, and some of them are already at the commercialization stage.

[0006] Conventional electrodes for secondary batteries have been manufactured using a wet process. However, when manufacturing electrodes using the wet process, a heat treatment process at high temperatures is required, which can damage the metal oxide. Therefore, there is an increasing need to develop electrodes manufactured using a dry process. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an electrode for a secondary battery having improved tensile strength and resistance reducing effect, a secondary battery including the same, and a method for manufacturing the electrode.

[0008] The problems to be solved by the present invention are not limited to those mentioned above, and problems not mentioned can be clearly understood by a person having ordinary skill in the art to which the present invention pertains from this specification and the accompanying drawings. [Means for solving the problem]

[0009] An electrode for a secondary battery according to one embodiment of the present invention includes an electrode current collector; and an electrode layer located on the electrode current collector, the electrode layer including a dry mixed electrode composition of an active material, a conductive material, and a binder, the binder including a first binder and a second binder, the first binder and the second binder being different from each other, and the second binder being attached to a surface of the first binder.

[0010] The glass transition temperature (T g ) is the glass transition temperature (T g ) may be higher.

[0011] The glass transition temperature (T g ) is 15 degrees Celsius or more and 100 degrees Celsius or less, and the glass transition temperature (T g ) may be 25° C. or more and 115° C. or less. The content of the binder may be 0.51 wt % or more and 11.99 wt % or less based on the total weight of the electrode composition.

[0012] The content ratio of the first binder to the second binder may be in the range of 0.1:10 to 10:0.1.

[0013] The first binder may include polytetrafluoroethylene (PTFE), and the second binder may include an acrylic polymer material.

[0014] The active material may include at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide, lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide having a spinel structure, LiMn2O4 in which a part of Li is replaced with an alkaline earth metal ion, a disulfide compound, Fe2(MoO4)3, and lithium manganese oxide (LMO). The electrode composition may be manufactured as a free-standing film, and the free-standing film may be attached onto the electrode current collector.

[0015] The free-standing film is 5kgf / cm 2 More than 50kgf / cm 2 It may have the following tensile strength:

[0016] According to another embodiment of the present invention, a method for manufacturing an electrode for a secondary battery includes the steps of dry-mixing an active material, a conductive material, and a binder to prepare a mixture; applying a shear force to the mixture to prepare an electrode composition; preparing a free-standing film from the electrode composition; and attaching the free-standing film onto an electrode current collector to form an electrode for a secondary battery, the binder including a first binder and a second binder, the first binder and the second binder being different from each other, and the second binder being attached to a surface of the first binder.

[0017] The glass transition temperature (T g ) is the glass transition temperature (T g ) may be higher.

[0018] The glass transition temperature (T g ) is 15 degrees Celsius or more and 100 degrees Celsius or less, and the glass transition temperature (T g The temperature may be 25° C. or more and 115° C. or less. The step of dry-mixing the active material, the conductive material, the first binder, and the second binder to prepare a mixture may be performed at room temperature, and the step of applying a shear force to the mixture to prepare an electrode composition may be performed at a temperature of 100° C. or more.

[0019] The content of the binder may be from 0.51 wt % to 11.99 wt % based on the total weight of the electrode composition.

[0020] The content ratio of the first binder to the second binder may be in the range of 0.1:10 to 10:0.1.

[0021] The first binder may include polytetrafluoroethylene (PTFE), and the second binder may include an acrylic polymer material.

[0022] The active material may include at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide, lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide having a spinel structure, LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, a disulfide compound, Fe2(MoO4)3, and lithium manganese oxide (LMO, lithium manganese oxide).

[0023] A secondary battery according to another embodiment of the present invention may include the above-described secondary battery electrode. Effect of the Invention

[0024] According to an embodiment of the present invention, by manufacturing an electrode for a secondary battery and a secondary battery including the same using an electrode composition including different binders, the tensile strength of the electrode can be improved, and the resistance reduction effect of the secondary battery including the electrode can be improved.

[0025] The effects of the present invention are not limited to the effects described above, and effects not mentioned can be clearly understood by a person having ordinary skill in the art to which the present invention belongs from this specification and the accompanying drawings. [Brief description of the drawings]

[0026] [Figure 1] FIG. 2 is a diagram showing an electrode composition of an electrode for a secondary battery according to one embodiment of the present invention. [Diagram 2] 2 is a flowchart illustrating a method for manufacturing an electrode for a secondary battery according to an embodiment of the present invention. [Diagram 3] 1 is a graph comparing the tensile strength and initial discharge capacity depending on the binder content of secondary battery electrodes in Examples of the present invention and Comparative Examples. [Figure 4] 1 is a graph comparing tensile strength and initial discharge capacity according to the content ratio of a first binder and a second binder in secondary battery electrodes in Examples and Comparative Examples of the present invention. [Diagram 5] 1 is a graph comparing the tensile strength and initial discharge capacity according to the glass transition temperatures of a first binder and a second binder of secondary battery electrodes in Examples and Comparative Examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.

[0028] Hereinafter, an electrode for a secondary battery according to one embodiment of the present invention will be described.

[0029] According to an embodiment of the present invention, an electrode for a secondary battery includes an electrode current collector, and an electrode layer formed as a free standing film on the electrode current collector. The electrode layer includes an electrode composition in which an active material, a conductive material, and a binder are dry-mixed.

[0030] The electrode layer is first manufactured as a free-standing film, and the free-standing film is attached to the electrode current collector and then formed by a lamination process. Here, the free-standing film has a resistance of 5 kgf / cm 2 More than 50kgf / cm 2 It may have the following tensile strength:

[0031] Therefore, the freestanding film may be in a state in which the active material, conductive material, first binder, and second binder contained in the electrode composition are mixed with each other with high binding strength, and the freestanding film may be easily stored in a roll form. Therefore, the productivity may be improved and the flexibility of the electrode may be improved. However, the tensile strength of the freestanding film may be less than 5 kgf / cm 2 If the thickness is less than 100 μm, cracks may occur between the electrode active materials in the electrode during charging and discharging, increasing the resistance and decreasing the electrical conductivity, resulting in a decrease in the life characteristics.

[0032] Hereinafter, each component included in an electrode for a secondary battery according to an embodiment of the present invention will be described in detail.

[0033] FIG. 1 is a diagram showing an electrode composition of an electrode for a secondary battery according to one embodiment of the present invention.

[0034] Referring to FIG. 1, the electrode for a secondary battery according to the present embodiment may include a first binder 100 and a second binder 200 as binders. The first binder 100 and the second binder 200 may be different from each other. Here, the first binder 100 and the second binder 200 serve to improve adhesion between active material particles and adhesive strength between the active material and the current collector, respectively. Here, the second binder 200 is attached to the surface of the first binder 100.

[0035] Therefore, in the electrode for a secondary battery according to an embodiment of the present invention, the first binders 100 are separated from each other by the second binder 200. Therefore, contact between the first binders 100 can be prevented, and the clumping phenomenon of the first binder 100 can be reduced. In addition, the bridging effect between the active material particles or between the active material particles and the current collector by the first binder 100 is not hindered, and the dispersibility of the first binder 100 can be improved, thereby improving the tensile strength and flexibility of the electrode.

[0036] As an example, the first binder 100 may include polytetrafluoroethylene (PTFE). Here, polytetrafluoroethylene (PTFE) has a characteristic that fibers are released from particles when a shear force is applied. That is, in the electrode for a secondary battery according to an embodiment of the present invention, a strong shear force is applied to an electrode composition including polytetrafluoroethylene (PTFE), and the electrode composition may be mixed by a physical mixing method by fiberizing polytetrafluoroethylene (PTFE).

[0037] Therefore, in the electrode for a secondary battery according to an embodiment of the present invention, the electrode composition may be mixed in a dry manner without a separate solvent or additive, and is very effective in bridging between active material particles or between active material particles and a current collector, while preventing damage to the active material that occurs during a heat treatment at high temperatures in a conventional mixing method.

[0038] For example, the second binder 200 may include an acrylic polymer material. Here, the acrylic polymer material may include an acrylic acid polymer and an acrylate polymer, and at least one of them may be selected and included. For example, the second binder 200 may include at least one of polyacrylic acid (PAA), methyl acrylate (MA), ethyl acrylate (EA), butyl acrylate (BA), ethylhexyl acrylate (EHA), and methyl methacrylate (MMA).

[0039] In addition, the glass transition temperature (T g ) is the glass transition temperature (T g ) of the second binder 200. g ) may be higher than room temperature. Generally, room temperature means a temperature with an error range of 5 degrees Celsius based on the standard temperature of 20 degrees Celsius.

[0040] More specifically, the glass transition temperature (T g ) is 15 degrees Celsius or more and 100 degrees Celsius or less, and the glass transition temperature (T g ) may be 25 degrees Celsius or more and 115 degrees Celsius or less. g ) is 15 degrees Celsius or more and 95 degrees Celsius or less, and the glass transition temperature (T g ) may be greater than or equal to 30 degrees Celsius and less than or equal to 110 degrees Celsius.

[0041] Here, the glass transition temperature (T g ) is generally measured by a measurement method such as DSC, DMA, or TMA. As an example, the present embodiment uses the glass transition temperature (T g The glass transition temperature (T g) crystals can be analyzed using the inflection point method.

[0042] Therefore, in the electrode for a secondary battery according to one embodiment of the present invention, the first binder 100 and the second binder 200 have glass transition temperatures in the above-mentioned ranges, and the second binder 200 adheres to the surface of the first binder 100 while not melted at room temperature, thereby preventing the first binder 100 from solidifying.

[0043] In addition, in the subsequent electrode manufacturing process, the temperature rises and the glass transition temperature (T g ) or more, the second binder 200 may dissolve, which may promote fiberization of the first binder 100, thereby causing bridging between the active material particles or between the active material particles and the current collector.

[0044] That is, the first binder 100 and the second binder 200 have a glass transition temperature (T g ) can effectively adjust the time when the first binder 100 is fiberized.

[0045] In contrast, the glass transition temperature (T g ) is the glass transition temperature (T g ), the second binder 200 melts before the first binder 100, and the second binder 200 remaining on the surface of the first binder 100 is reduced or eliminated. In this case, there is no problem in that the time point at which the first binder 100 is fiberized cannot be controlled, and the glass transition temperature (T g If the temperature is lower than room temperature, the fiberization of the first binder 100 proceeds at room temperature, and it is difficult to prevent the first binder 100 from solidifying.

[0046] In addition, the glass transition temperatures (T g) is lower than the above-mentioned temperature range, at least a part of the second binder 200 melts at room temperature, the fiberization of the first binder 100 proceeds at room temperature, and it is difficult to prevent the solidification of the first binder 100. As a result, the bridging effect between particles in the electrode composition is reduced, and the tensile strength may also be significantly reduced.

[0047] Conversely, the glass transition temperatures (T g ) is higher than the above-mentioned temperature range, additional manufacturing time and equipment are required in the process of raising the temperature to melt the first binder 100 and the second binder 200 in the electrode manufacturing process, and fiberization of the first binder 100 cannot be promoted.

[0048] Also, the content of Binder 100,200 may be 0.51 wt% to 11.99 wt% based on the total weight of the electrode composition. More preferably, the content of Binder 100,200 may be 1 wt% to 11 wt% based on the total weight of the electrode composition. For example, the content of Binder 100,200 may be 1 wt% to 10 wt% based on the total weight of the electrode composition.

[0049] Therefore, the secondary battery electrode according to the present embodiment contains the binder 100, 200 in the above-mentioned range, and can maximize the fiberization of the binder, and has excellent bridging effect between particles in the electrode composition and excellent tensile strength. In addition, the binder can be prevented from solidifying and its dispersibility can be improved, and the electrode containing the electrode composition has an excellent resistance reduction effect.

[0050] On the other hand, if the content of the binders 100 and 200 is less than 0.51% by weight, the bridging effect between particles in the electrode composition is reduced and the tensile strength may also be significantly reduced. Also, if the content of the binders 100 and 200 is more than 11.99% by weight, the first binder 100 and the second binder 200 act as resistors in an electrode containing the electrode composition, making it difficult to expect high output.

[0051] Furthermore, the content ratio of the first binder 100 to the second binder 200 may be 0.1:10 to 10:0.1. More preferably, the content ratio of the first binder 100 to the second binder 200 may be 0.5:10 to 10:0.5. As an example, the content ratio of the first binder 100 to the second binder 200 may be 1:10 to 10:1.

[0052] Therefore, the electrode for a secondary battery according to the present embodiment contains the first binder 100 and the second binder 200 in the above-mentioned range, and can maximize the fiberization of the binder, and has excellent bridging effect between particles in the electrode composition and excellent tensile strength. In addition, the binder can be prevented from solidifying and its dispersibility can be improved, and the electrode containing the electrode composition has an excellent effect of reducing the resistance.

[0053] On the other hand, when the content ratio of the first binder 100 to the second binder 200 is less than 0.1:more than 10, the degree of fiberization of the binder is reduced, and it is impossible to manufacture an electrode when only the second binder 200 is included. In addition, when the content ratio of the first binder 100 to the second binder 200 is more than 10:less than 0.1, the binder often hardens, reducing the effect of reducing the resistance of the electrode and possibly reducing the battery performance.

[0054] The active material may be a positive electrode active material, and examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide, lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, disulfide compound, Fe2(MoO4)3, and the like.

[0055] For example, the active material may include lithium manganese oxide (LMO). Here, the active material may be included in an amount of 85 wt% to 99 wt% based on the total weight of the electrode composition. More preferably, the active material may be included in an amount of 87 wt% to 98 wt% based on the total weight of the electrode composition. For example, the active material may be included in an amount of 89 wt% to 97 wt% based on the total weight of the electrode composition.

[0056] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, graphene, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. Here, the conductive material can be included in an amount of 1% by weight to 10% by weight based on the total weight of the electrode.

[0057] The above-described secondary battery electrode may be included as a positive electrode in a secondary battery according to another embodiment of the present invention. More specifically, the secondary battery according to another embodiment of the present invention may include an electrode assembly including the positive electrode, the negative electrode, and a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0058] The negative electrode, like the secondary battery electrode, is prepared by coating a negative electrode current collector with a negative electrode slurry containing a negative electrode active material, a polymer material, a conductive material, and the like.

[0059] The negative electrode may also be prepared by attaching or coating a negative electrode slurry containing a negative electrode active material onto a negative electrode current collector, and the negative electrode slurry may further include a conductive material and a polymer material as described above, together with the negative electrode active material.

[0060] The negative active material may be any negative active material for lithium secondary batteries commonly used in the art, such as lithium metal, lithium alloy, petroleum coke, activated carbon, graphite, silicon, tin, metal oxides, or other carbonaceous materials.

[0061] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used.

[0062] The separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move, and can be used without any particular limitation as long as it can be used as a separator in a normal lithium secondary battery, and is particularly preferably one that has low resistance to the ion movement of the electrolyte and has excellent electrolyte humidification ability. The electrolyte used in the present invention includes, but is not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, and the like that can be used in the manufacture of lithium secondary batteries.

[0063] Specifically, the electrolyte may include an organic solvent and a lithium salt. The organic solvent may be any organic solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. The lithium salt may be any lithium salt that can provide lithium ions used in the lithium secondary battery.

[0064] In addition to the above components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, trimethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0065] 2 is a flow chart showing a method for manufacturing an electrode for a secondary battery according to an embodiment of the present invention. Referring to FIG. 2, the method for manufacturing an electrode according to the present embodiment includes a premixing step (S10) of mixing an active material, a conductive material, and a binder, a mixing step (S20) of preparing an electrode composition by applying high shear force, a step (S30) of preparing a free-standing film using the electrode composition, and a step (S40) of attaching the free-standing film onto an electrode current collector and then manufacturing an electrode through a lamination process.

[0066] In the premixing step (S10), the active material, the conductive material, and the binder are mixed in a dry state. The binder includes a first binder and a second binder, and the first binder and the second binder may be different from each other. The second binder is attached to a surface of the first binder.

[0067] The present invention will be described below with reference to more specific examples. However, the following examples are provided to illustrate the present invention, and the scope of the present invention is not limited thereto.

[0068] <Example 1> A premixing step (S10) was carried out to prepare a mixture by dry mixing the active material, conductive material, first binder, and second binder using a Waring blender, where the active material was 92 wt% lithium manganese oxide (LMO) and the conductive material was 2 wt% Super C65.

[0069] The total content of the first binder, which is polytetrafluoroethylene (PTFE), and the second binder, which is an acrylic polymer, is 6% by weight. The content ratio of the first binder 100 to the second binder 200 is 70:30. The glass transition temperature (T g ) is 34 degrees Celsius, and the glass transition temperature (T g ) is 55 degrees Celsius. At this time, the premixing step (S10) was carried out at 5000 rpm at room temperature for 1 minute.

[0070] Thereafter, a mixing step (S20) was performed to prepare an electrode composition by applying shear force to the mixture prepared in the premixing step (S10) using PBV-0.1L equipment of Irie Shokai Co., Ltd. At this time, the mixing step (S20) was performed at 30 rpm and 100 degrees Celsius for 5 minutes.

[0071] <Example 2> In the first embodiment, the content ratio of the first binder 100 to the second binder 200 is 40:60. g ) is 40 degrees Celsius. Except for this, the electrode composition was produced in the same manner as in Example 1.

[0072] <Example 3> In Example 1, the active material was 97 wt % lithium manganese oxide (LMO), and the total content of the first binder 100 and the second binder 200 was 1 wt %. Except for this, an electrode composition was prepared in the same manner as in Example 1.

[0073] <Example 4> In Example 1, the active material was 88 wt % lithium manganese oxide (LMO), and the total content of the first binder 100 and the second binder 200 was 10 wt %. Except for this, an electrode composition was prepared in the same manner as in Example 1.

[0074] <Example 5> In the first embodiment, the glass transition temperature (T g ) is 90 degrees Celsius, and the glass transition temperature (T g ) is 106 degrees Celsius. Except for this, the electrode composition was produced in the same manner as in Example 1.

[0075] <Comparative Example 1> In Example 1, the active material was 97.5 wt % lithium manganese oxide (LMO), and the total content of the first binder 100 and the second binder 200 was 0.5 wt %. Except for this, an electrode composition was prepared in the same manner as in Example 1.

[0076] <Comparative Example 2> In Example 1, the active material was 86 wt % lithium manganese oxide (LMO), and the total content of the first binder 100 and the second binder 200 was 12 wt %. Except for this, an electrode composition was prepared in the same manner as in Example 1.

[0077] <Comparative Example 3> In the first embodiment, the content ratio of the first binder 100 to the second binder 200 is 100:0. In addition, the glass transition temperature (T g ) is 25 degrees Celsius. Except for this, the electrode composition was produced in the same manner as in Example 1.

[0078] <Comparative Example 4> In the first embodiment, the content ratio of the first binder 100 to the second binder 200 was 0:100. Except for this, the electrode composition was prepared in the same manner as in the first embodiment.

[0079] <Comparative Example 5> In the first embodiment, the glass transition temperature (T g ) is −10 degrees Celsius, and the glass transition temperature (T g ) is −40° C. Except for this, the electrode composition was prepared in the same manner as in Example 1.

[0080] <Comparative Example 6> In the first embodiment, the glass transition temperature (T g ) is 11 degrees Celsius, and the glass transition temperature (T g ) is −12° C. Except for this, the electrode composition was prepared in the same manner as in Example 1.

[0081] <Comparative Example 7> In the first embodiment, the glass transition temperature (T g ) is 110 degrees Celsius, and the glass transition temperature (T g ) is 120 degrees Celsius. Except for this, the electrode composition was produced in the same manner as in Example 1.

[0082] <Experimental Example 1 (Measurement of Tensile Strength)> 2, the electrode compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were subjected to a free-standing film preparation step (S30) in which a free-standing film having a length of 20 mm and a width of 20 mm was prepared using a roll mill facility manufactured by Inoue Manufacturing Co., Ltd. Both ends of each of the prepared free-standing films were fixed with a jig, and the tensile strength of each of the free-standing films was measured at a speed of 50 mm / min using a UTM facility manufactured by Instron Co., Ltd., and the results are shown in Table 1.

[0083] [Table 1]

[0084] <Experimental Example 2 (Discharge Capacity Measurement)> Referring to FIG. 2, for Examples 1 to 5 and Comparative Examples 1 to 6, the free-standing films prepared in Experimental Example 1 were roll-pressed onto a current collector made of aluminum foil, and then the loading value was 5 mAh / cm 2 An electrode preparation step (S40) was performed to prepare a positive electrode with a porosity of 30%. Then, a coin half cell was prepared by using a lithium metal having a thickness of 200 μm as a negative electrode together with each prepared positive electrode. Then, the discharge capacity value of the first cycle after charging and discharging at 0.1C / 0.1C in the voltage range of 3.0~4.3V for each prepared coin half cell was calculated, and the results are shown in Table 2.

[0085] [Table 2]

[0086] <Experimental Results Analysis> 3 is a graph comparing the tensile strength and initial discharge capacity according to the binder content of the secondary battery electrode in the examples of the present invention and the comparative examples. In particular, FIG. 3 is a graph comparing the tensile strength and initial discharge capacity of Example 1, Example 3, Example 4, Comparative Example 1, and Comparative Example 2 among the results shown in Tables 1 and 2. In this case, Comparative Example 1, Example 3, Example 1, Example 4, and Comparative Example 2 have the same content ratio of the first binder and the second binder, but the total content of the first binder 100 and the second binder 200 increases in the order of Comparative Example 1, Example 3, Example 1, Example 4, and Comparative Example 2. In the case of Comparative Example 1, the total content of the first binder 100 and the second binder 200 is 0.5% by weight, which is smaller than that of the Examples, and in the case of Comparative Example 2, the total content of the first binder 100 and the second binder 200 is 12% by weight, which is larger than that of the Examples.

[0087] Referring to FIG. 3, it can be seen that as the total content of the first binder 100 and the second binder 200 increases, the tensile strength is excellent but the initial discharge capacity decreases. That is, if the total content of the first binder 100 and the second binder 200 is too small, there is a problem of the tensile strength decreasing. Also, if the total content of the first binder 100 and the second binder 200 is too large, there is a problem of the initial discharge capacity decreasing because the resistance of the binder increases due to the increase in the binder content. Therefore, it can be seen that, when the total content of the first binder 100 and the second binder 200 is as in Example 1, Example 3, and Example 4, the tensile strength and the initial discharge capacity are all generally excellent.

[0088] FIG. 4 is a graph comparing the tensile strength and initial discharge capacity according to the content ratio of the first binder and the second binder in the secondary battery electrode in the examples and comparative examples of the present invention. In particular, FIG. 4 is a graph comparing the tensile strength and initial discharge capacity of Example 1, Example 2, Comparative Example 3, and Comparative Example 4 among the results shown in Tables 1 and 2. Here, Example 1, Example 2, Comparative Example 3, and Comparative Example 4 have the same total content of the first binder 100 and the second binder 200, but the content ratio is different from each other. Here, the content of the first binder gradually increases and the content of the second binder gradually decreases in the order of Comparative Example 4, Example 2, Example 1, and Comparative Example 3.

[0089] 4, first, when the binder contains only the second binder as in Comparative Example 4, it is difficult to manufacture an electrode during dry mixing, and therefore the tensile strength and initial discharge capacity cannot be measured. Therefore, it can be confirmed that the first binder is essential for the electrode for a secondary battery according to the present invention.

[0090] 4, it can be seen that the tensile strength and initial discharge capacity are both decreased when only the first binder is included in the binder as in Comparative Example 3. This is because when the first binder is used alone, the first binder solidifies at room temperature, reducing the bridging effect between particles and increasing the resistance.

[0091] Therefore, when the content ratio of the first binder 100 and the second binder 200 is as in Example 1 and Example 2, it can be confirmed that the tensile strength and the initial discharge capacity are all excellent overall.

[0092] FIG. 5 is a graph comparing the tensile strength and initial discharge capacity according to the glass transition temperature of the first binder and the second binder of the secondary battery electrode in the embodiment and the comparative example of the present invention. In particular, FIG. 5 is a graph comparing the tensile strength and initial discharge capacity of Example 1, Example 5, Comparative Example 5, and Comparative Example 6 among the results shown in Tables 1 and 2. Here, Example 1, Example 5, Comparative Example 5, Comparative Example 6, and Comparative Example 7 all have the same content and content ratio of the first binder 100 and the second binder 200, but the glass transition temperatures of the first binder 100 and the second binder 200 are different. Here, the glass transition temperatures of the first binder 100 and the second binder 200 increase in the order of Comparative Example 5, Comparative Example 6, Example 1, Example 5, and Comparative Example 7. At this time, the tensile strength and initial discharge capacity of Comparative Example 7 were not measured, and are omitted in FIG. 5.

[0093] Referring to FIG. 5, it can be seen that as the glass transition temperatures of the first binder 100 and the second binder 200 increase, the tensile strength and the initial discharge capacity gradually increase.

[0094] That is, when the glass transition temperatures of the first binder 100 and the second binder 200 are excessively low as in Comparative Examples 5 and 6, the second binder 200 melts at room temperature, and the second binder 200 may not adhere well to the surface of the first binder 100. Therefore, when the second binder 200 having an excessively low glass transition temperature is included, there is a problem that it becomes difficult to prevent the solidification phenomenon of the first binder 100 that occurs at room temperature.

[0095] In addition, when the glass transition temperature of the second binder 200 is lower than that of the first binder 100, as in Comparative Examples 5 and 6, there is a problem that the second binder 200 melts before the first binder 100, making it more difficult to prevent the first binder 100 from solidifying.

[0096] Also, referring to Tables 1 and 2, it can be seen that when the glass transition temperatures of the first binder 100 and the second binder 200 are excessively high as in Comparative Example 7, the first binder 100 is not fiberized at the process temperature, and the tensile strength and initial discharge capacity cannot be measured. Therefore, it can be seen that when the first binder 100 and the second binder 200 have a glass transition temperature as in Examples 1 and 5, the solidification of the first binder 100 is effectively prevented, excellent fiberization is performed, and the tensile strength and initial discharge capacity are all generally excellent.

[0097] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention.

Claims

1. An electrode current collector, and an electrode layer disposed on the electrode current collector; The electrode layer comprises a dry mixed electrode composition of an active material, a conductive material, and a binder; the binder includes a first binder and a second binder, the first binder and the second binder being different types of binders from each other; the second binder is attached to a surface of the first binder; the first binder comprises polytetrafluoroethylene (PTFE); the second binder has a glass transition temperature (Tg) higher than the glass transition temperature (Tg) of the first binder; The glass transition temperature (Tg) of the first binder is 15 degrees Celsius or more and 100 degrees Celsius or less, The second binder has a glass transition temperature (Tg) of 25° C. or more and 115° C. or less; The content of the binder is 0.51 wt % or more and 11.99 wt % or less based on the total weight of the dry mixed electrode composition.

2. The electrode for a secondary battery according to claim 1 , wherein a content ratio of the first binder to the second binder is in the range of 0.1:10 to 10:0.

1.

3. The electrode for a secondary battery according to claim 1 , wherein the second binder contains an acrylic polymer material.

4. The active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide, lithium copper oxide (Li 2 CuO 2 ), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn 2 O 4 , disulfide compound, Fe 2 (MoO 4 ) 3 4. The electrode for a secondary battery according to claim 1, further comprising at least one of a lithium manganese oxide (LMO) and a lithium manganese oxide (LMO).

5. the dry mixed electrode composition is a free-standing film; The electrode for a secondary battery according to claim 1 , wherein the free-standing film is attached onto the electrode current collector.

6. The free-standing film has a strength of 5 kgf / cm 2 More than 50kgf / cm 2 6. The electrode for a secondary battery according to claim 5, having a tensile strength of:

7. dry mixing an active material, a conductive material, and a binder to produce a mixture; applying a shear force to the mixture to produce an electrode composition; preparing a free-standing film from the electrode composition; and The free-standing film is attached onto an electrode collector to form an electrode for a secondary battery; the binder includes a first binder and a second binder, the first binder and the second binder being different types of binders from each other; the second binder is attached to a surface of the first binder; the first binder comprises polytetrafluoroethylene (PTFE); the second binder has a glass transition temperature (Tg) higher than the glass transition temperature (Tg) of the first binder; The glass transition temperature (Tg) of the first binder is 15 degrees Celsius or more and 100 degrees Celsius or less, The second binder has a glass transition temperature (Tg) of 25° C. or more and 115° C. or less; a total content of the first binder and the second binder is from 0.51 wt % to 11.99 wt % based on a total weight of the electrode composition.

8. The step of dry-mixing the active material, the conductive material, the first binder, and the second binder to prepare a mixture is performed at room temperature; The method of claim 7 , wherein the step of applying a shear force to the mixture to prepare an electrode composition is performed at a temperature of 100° C. or higher.

9. 9. The method for manufacturing an electrode for a secondary battery according to claim 7, wherein a content ratio of the first binder to the second binder is in the range of 0.1:10 to 10:0.

1.

10. The method for manufacturing an electrode for a secondary battery according to claim 7 , wherein the second binder contains an acrylic polymer material.

11. The active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide, lithium copper oxide (Li 2 CuO 2 ), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn 2 O 4 , disulfide compound, Fe 2 (MoO 4 ) 3 11. The method for producing an electrode for a secondary battery according to claim 7, wherein the electrode contains at least one of lithium manganese oxide (LMO).

12. A secondary battery comprising the electrode for a secondary battery according to claim 1 .

Citation Information

Patent Citations

  • An electrode membrane, its preparation method and uses

    CN112038574B

  • Electrochemical element electrode material and composite particle

    JP2012129536A

  • Dry electrode of energy storage device and manufacturing method thereof

    JP2019216101A

  • Positive electrode, lithium secondarty battery comprising the positive electrode, and method for manufacturing the positive electrode

    KR1020180121411A

  • Compositions and methods for dry electrode films including microparticulate non-fibrillizable binders

    US20190305316A1